The unbeatable Squirrel Girl. Vol. 2, Squirrel you know it's true - North, Ryan, 1980- (Marvel now!, 2015)
When Squirrel Girl meets Chipmunk Hunk, Koi Boi, and Girl Squirrel, she hopes she's met some new allies, but she has her doubts about Girl Squirrel. And the world's fate is at risk when Ratatoskr, the Norse God of Squirrels, attacks.